Comparação entre diferentes interpoladores na delimitação de bacias hidrográficas - Redivo, André Luciancencov (2002)
The morphometric parameters are of fundamental importance for the good operation of models, among them, the area of the basin to amount determined for each pixel stands out for releases use in hydrologic models used for the definition of saturation areas in the landscape and predictive models of mass movements. In this work three different ways are compared of obtaining the delimitation of hydrologic basins starting from a digital elevation model: a) Directly of DEM without any treatment type, being used of different interpolators types; b) Starting from the elimination of the depressions inherent of the depressions inherent of the interpolador thats doesn't correspond to the nature and; c) Marking DEM being used of the corresponding vectors the drainage net and water bodies, being elimininated, also, the depressions. The results shows that the values obtained by the different processes possess significant discrepancy amongst themselves.